THE ROLE OF FEEDBACK LITERACY IN IMPROVING ASSESSMENT OUTCOMES IN EFL CONTEXTS - Samiyeva Nazokat Olim qizi; Khonsaidova Maktuba Makhamadalievna (TADQIQOTLAR, 2026)
ABSTRACT   Feedback literacy plays a crucial role in improving assessment outcomes in EFL contexts by enabling learners to understand, interpret, and effectively use feedback for learning  improvement.  In  many  EFL  settings,  students  often  fail  to  engage meaningfully with feedback, limiting its impact on language development. This paper highlights the importance of developing feedback-literate learners who can actively reflect  on  and  act  upon  feedback  to  enhance  their  performance.  It  argues  that integrating  feedback  literacy  into  classroom  practice  promotes  learner  autonomy, deeper engagement with assessment, and improved language proficiency.